2008
DOI: 10.1007/s10585-008-9233-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of the MTA family and their encoded proteins in human cancers: molecular functions and clinical implications

Abstract: MTA (metastasis-associated gene) is a newly discovered family of cancer progression-related genes and their encoded products. MTA1, the first gene found in this family, has been repeatedly reported to be overexpressed along with its protein product MTA1 in a wide range of human cancers. In addition, the expression of MTA1/MTA1 correlates with the clinicopathological properties (malignant properties) of human cancers. MTA proteins are transcriptional co-repressors that function in histone deacetylation and are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
192
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(200 citation statements)
references
References 80 publications
6
192
1
1
Order By: Relevance
“…Inhibition of cancer cell migration by TBX5 may result from upregulating MTSS1 and downregulating MTA2. Similar findings were reported by others that antimetastatic MTSS1 and pro-metastatic MTA2 were correlated with the metastatic potential of certain types of cancers (Hicks et al, 2006;Parr and Jiang, 2009;Toh and Nicolson, 2009). Thus, through modulating these important genes, TBX5 exerted antitumorigenesis effect by promoting apoptosis and suppressing cell proliferation and metastasis.…”
Section: T-box Transcription Factor 5 In Colon Cancer J Yu Et Alsupporting
confidence: 90%
“…Inhibition of cancer cell migration by TBX5 may result from upregulating MTSS1 and downregulating MTA2. Similar findings were reported by others that antimetastatic MTSS1 and pro-metastatic MTA2 were correlated with the metastatic potential of certain types of cancers (Hicks et al, 2006;Parr and Jiang, 2009;Toh and Nicolson, 2009). Thus, through modulating these important genes, TBX5 exerted antitumorigenesis effect by promoting apoptosis and suppressing cell proliferation and metastasis.…”
Section: T-box Transcription Factor 5 In Colon Cancer J Yu Et Alsupporting
confidence: 90%
“…15 Alternatively, RSF-1 overexpression may directly contribute to tumor invasiveness and metastasis. In fact, recent studies have indicated that certain proteins contributing to metastasis, such as metastasis-associated gene in NuRD complex 25 or MYC and BRCA1 in SWI/SNF complex, 26,27 can form functional complexes with chromatin remodeling factors in promoting cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Each MTA member modifies the functional specificities of the Mi2/NuRD complexes relevant to its upstream and downstream signaling pathways and molecular targets. Specifically, MTA1 is expressed at high levels in metastatic cancer cells and its ectopic overexpression in mouse mammary epithelial cells can induce mammary epithelial proliferation and tumorigenesis [27,29,30]. In addition, MTA1 serves as a transcriptional corepressor of estrogen receptor α (ERα) [31].…”
Section: Introductionmentioning
confidence: 99%